On the Verge of Collapse: The German Economy during World War I (KULT_online, 2023)
A well-founded overview that does justice to its scientific value: With his handbook on the German economy in World War I, Marcel Boldorf not only presents the latest research results, but also shows, based on the various economic sectors, that the German state took on a new role between 1914 and 1918. In 23 well-written articles, the authors provide insights into one of the most blatant structural breaks in European economic history. Worth reading!